ANALISIS IMPLEMENTASI KEBIJAKAN ZONASI DALAM PENERIMAAN PESERTA DIDIK BARU PADA JENJANG SMP DI JAKARTA TIMUR - Wanda Wulandari; Lukmanul Hakim; Hanny Purnamasari (LPPM Universitas Abdurrab, 2026)
This study analyzes the implementation of the zoning system policy in the New Student Admission (PPDB) for junior high schools in East Jakarta. The study aims to examine the extent to which the zoning system policy is applied in the PPDB process. The study uses a qualitative approach with a case study method and is analyzed using Van Meter and Van Horn's policy implementation theory, which includes six indicators, namely (1) policy standards and objectives, (2) resources, (3) characteristics of implementing agents, (4) implementers' dispositions, (5) interorganizational communication, and (6) social, economic, and political environments. The results show that the implementation of the zoning system policy has generally been able to expand spatial and social equity in access to education. However, in its implementation, a number of obstacles were still found, such as disparities in academic quality between schools, limited PPDB implementing human resources, low digital literacy among the community, and the practice of manipulating domicile data. These findings imply the need to strengthen policies by improving population administration supervision, equalizing educational resources, and increasing the capacity of implementers and the digital literacy of the community so that the objectives of the zoning system can be optimally achieved.